Progression and incidence of myopia among schoolchildren in the post-COVID-19 pandemic period: a prospective cohort study in Shantou, China - Li Luo; Mingzhi Zhang; Kunliang Qiu; Yuancun Li; Chengyao Guo; Jianwei Lin (BMJ Open, 2023)
Objectives To determine the progression and incidence of myopia in Chinese schoolchildren in the post-COVID-19 pandemic period in Shantou, China.Design Prospective cohort study.Setting Shantou Myopia Study, China.Participants 1-year follow-up data were available for 621 881 schoolchildren (301 999 females). Data on spherical equivalent refraction (SER) were collected.Primary and secondary outcome measures The primary outcomes were myopia progression and incidence. Myopia progression is defined as a change of SER towards the negative direction in the follow-up visit. Incidence is defined as the proportion of schoolchildren who were not myopic but developed myopia in the follow-up study. Age, sex and SER at baseline were evaluated as associated factors for myopia burden, which were defined as the secondary outcomes.Results Mean progression of SER was −0.35±0.97 D for the population (ranging from −0.06 D at 18 years of age to −0.46 D at 11 years of age), with a rapid myopic progression for students at the age of 10–12 years (−0.50 D in girls and −0.44 D in boys). A myopic shift greater than −0.50 D/year occurred in 256 299 eyes (41.21%). Myopic progression in refraction was associated with the 10–12 years age groups (OR 1.42; 95% CI 1.39 to 1.45, p<0.001), female sex (OR 1.09; 95% CI 1.08 to 1.10, p<0.001) and higher refractive errors at baseline (OR>1.00, p<0.001). The annual incidence of myopia among schoolchildren was 24.85%, with an incidence of 26.69% in girls and 23.02% in boys.Conclusions Our study revealed an annual myopia progression of −0.35 D and an incidence of 24.85% among schoolchildren in the post-COVID-19 pandemic period. Myopia progressed rapidly at 10–12 years of age, with −0.50 D in girls and −0.44 D in boys. The incidence was higher for children aged 10–11 years and for girls.